2021
DOI: 10.3389/fneur.2021.752762
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cerebral Blood Flow and Functional Connectivity Strength in Subjects With White Matter Hyperintensities

Abstract: White matter hyperintensities (WMHs) are common neuroimaging findings in the aging population and are associated with various clinical symptoms, especially cognitive impairment. Abnormal global cerebral blood flow (CBF) and specific functional connections have been reported in subjects with higher WMH loads. Nevertheless, the comprehensive functional mechanisms underlying WMH are yet to be established. In this study, by combining resting-state functional magnetic resonance imaging and arterial spin labeling, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…43,44 Furthermore, WMHs are usually accompanied by other damages in the brain, including cortical microinfarcts and cerebral microbleeds, which may lead to the lower blood supply required by global brain tissues. 39 In line with previous findings, our study suggested that although we did not include WMHs regions in the CBF calculation, the decreased CBF in women during menopause transition and after menopause transition may be largely due to the increased proportions of WMHs affecting the whole brain perfusion hemodynamics.…”
Section: Figure Cerebral Blood Flow (Cbf) Between Age-matched Men And...supporting
confidence: 88%
See 1 more Smart Citation
“…43,44 Furthermore, WMHs are usually accompanied by other damages in the brain, including cortical microinfarcts and cerebral microbleeds, which may lead to the lower blood supply required by global brain tissues. 39 In line with previous findings, our study suggested that although we did not include WMHs regions in the CBF calculation, the decreased CBF in women during menopause transition and after menopause transition may be largely due to the increased proportions of WMHs affecting the whole brain perfusion hemodynamics.…”
Section: Figure Cerebral Blood Flow (Cbf) Between Age-matched Men And...supporting
confidence: 88%
“…37 Previous studies have demonstrated decreased CBF and delayed arterial transit time associated with WMH. 30,[38][39][40] The underlying mechanisms may be that WMHs reflect white matter atrophy with fewer cells, or damage to the neural fiber and local blood vessels, which are associated with regional hypoperfusion. 41 A recent study has demonstrated an accelerated increase in WMH, and a higher burden of WMH in women after menopause, compared with premenopausal women and men of similar age, 42 which was in accordance with the higher proportions of WMHs in perimenopausal and postmenopausal groups in the current study.…”
Section: Figure Cerebral Blood Flow (Cbf) Between Age-matched Men And...mentioning
confidence: 99%
“…In fact, while Lei et al (2021) were able to relate the DAN-DMN anti-correlation to the poor modulation of attentional processes in response to shifting cognitive demands, here we added the notion that such an unbalance in the neural resource management could be linked to defective NVC within and across the two networks, as discussed above. Thus, as far as future studies will confirm the neurovascular origin of this unbalance, it would be more than likely that these neural effects can occur in the earliest stages of cognitive decline, i.e., before the cognitive impairment becomes manifest at the clinical evaluation ( Gorelick et al, 2016 ; Cheng et al, 2021 ; Huang et al, 2021 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…3D-ASL permits non-invasive quantification of CBF and has good reliability and repeatability ( 45 ). One study reported that greater WMH severity was associated with lower average CBF of whole-brain white matter and CBF at and around the lesion ( 42 , 46 ). A quantitative study of CBF in patients with different degrees of WMH using 3D-ASL revealed that CBF in WMH was lower than that in the surrounding tissues, and whole-brain CBF in patients with confluent WMH was 20% lower than that in patients with spotted or newly confluent WMH ( 47 ).…”
Section: Application Of Multimodal Mri Techniques For Wmh and Cogniti...mentioning
confidence: 99%